Curriculum development in the postmodern era teaching and learning in an age of accountability - Slattery, Patrick, 1953- (Routledge, 2013)
"The 3rd edition of this introduction to and analysis of contemporary concepts of curriculum that emerged from the Reconceptualization of curriculum studies brings readers up to date on the major research themes within the historical development of the field"--